Métodos de aprendizagem automática: um estudo baseado na avaliação e previsão de clientes bancários - Serras, Flávia Alexandra Jorge (2016)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence